The BB Wistar Rat as a Diabetic Model for Fracture Healing. (31st March 2013) - Sood, Amit; Cunningham, Catie; Lin, Sheldon
Abstract : The advent of improved glucose control with insulin and oral medications has allowed for the diabetic population to live longer and healthier lives. Unfortunately diabetes remains a worldwide epidemic with multiple health implications. Specifically, its affects upon fracture healing have been well studied and shown to have negative effects on bone mineral density, biomechanical integrity, and fracture healing. Multiple animal models have been used for research purposes to gain further insight into the effects and potential treatments of this disease process. The diabetic BB Wistar rat is one model that replicates a close homology to human type-1 diabetes and has been used as a fracture model to study the effects of diabetes on bone integrity and healing. In particular, the effects of tight glucose control, ultrasound therapy, platelet-rich plasma (PRP), platelet-derived growth factor (PDGF), bone morphogenetic protein 2 (BMP-2), and allograft bone incorporation have been studied extensively. We present a review of the literature using the BB Wistar rat to elucidate the implications of diabetes on fracture healing.